Broadband emission and flat optical gain glass containing Ag aggregates for tunable laser. Issue 3 (27th August 2018) - Zhong, Hua; Chen, Baojiu; Fu, Shaobo; Li, Xiangping; Zhang, Jinsu; Xu, Sai; Zhang, Yanqiu; Tong, Lili; Sui, Guozhu; Xia, Haiping
Abstract: Spectroscopic properties of Sm 3+ ‐doped borate glass with silver aggregates were investigated, and it was found that the glass presented broad excitation and emission band covering violet‐infrared region. Furthermore, the optical gain coefficients at various wavelengths were measured via an amplified spontaneous emission technique, it was confirmed that the glass displayed flat net optical gain coefficient in almost full visible region. In addition, the fluorescent temperature quenching of the glass was examined, and it was seen that about 50% of room temperature emission intensity was kept when the sample was heated up to 325°C.